Impact of the CaCl2 content in the rehydration media on the microcapsule formation out of spray dried capsule precursors for the immobilization of probiotic bacteria. (May 2017) - Würth, R.; Wiesner, S.; Foerst, P.; Kulozik, U.
Abstract: The aim of this work was to develop a capsule formation process at moderate temperatures with a high encapsulation yield (EY) of probiotic bacteria. Capsule precursors (CP) obtained by spray drying were rehydrated at 40 °C in aqueous solution to form water-insoluble hydrogel capsules. The CaCl2 concentration (0–2 mm ) in the rehydration solution was varied. The rehydration step was evaluated regarding matrix stability and capsule size. The results show that only low amounts of non-aggregated casein remain in the rehydration media at or above 1.3 mm CaCl2 . Additionally, under this condition the particle size distribution shows no particles with the size of non-aggregated caseins and bacteria. Both results indicate a completely, stable matrix structure. To gain a deeper understanding the EY and capsule morphology by scanning electron microscope (SEM) images were assessed. The SEM images show that the bacterial cells are fully embedded in a dense casein network structure. The determined EY was ∼85%.